An inflammation self-adaptive nanocarrier for highly efficient gene therapy. (September 2020) - Jia, H.; Yang, Y.; Li, M.; Li, Y.; Han, X.; Li, J.; Zhang, X.; Fan, C.; Wu, T.; Cui, C.; Wei, X.; Liu, W.
Abstract: Inflammation represents a real micromilieu of many diseases as well as the actual application environment of nanocarriers. However, few studies have focused on the influence of the inflammatory environment on the effects of nanoparticle delivery. Herein, a novel inflammation self-adaptive nanocarrier is designed and fabricated by attaching the ascorbyl palmitate (AP) onto the surface of gene-entrapped polymeric nanocomplexes through the formation of phenylboronate bond. In vitro and in vivo studies demonstrate that the introduction of AP enhances considerably the accumulation of entrapped gene in inflammation and facilitates the intracellular uptake of gene-loading nanoparticles. Meanwhile, the gene transfection efficiency of DNA and in vivo gene therapy of nanocomplexes under an inflammation stimulus is significantly enhanced. Hence, our delicate design concept opens up a new pathway to develop an inflammation self-adaptive drug delivery system for precise drug/gene delivery and therapy. Graphical abstract: Image 1 Highlights: An inflammation self-adaptive gene nanocarrier was synthesized with high cellular uptake and gene transfection efficiency. Ascorbyl palmitate (AP) was introduced by self-assembly method, thus enhancing the gene therapy efficiency under inflammation. The nanotechology opens a new pathway to establish inflammation self-adaptive multipurpose nanoplatforms.